Efficacy of atezolizumab plus bevacizumab for unresectable HCC: Systematic review and meta-analysis of real-world evidence - Giulia Francesca Manfredi; Claudia Angela Maria Fulgenzi; Ciro Celsa; Bernardo Stefanini; Antonio D'Alessio; Matthias Pinter; Bernhard Scheiner; Nichola Awosika; Leonardo Brunetti; Pasquale Lombardi; Charles Latchford; Pei-Chang Lee; et al. (JHEP Reports, 2025)
Background & Aims: Atezolizumab plus bevacizumab (A+B) is a standard-of-care treatment in unresectable hepatocellular carcinoma (uHCC). Verification of its effectiveness outside clinical trials is an area of unmet need, especially in estimating long-term survival outcomes. Methods: We conducted a systematic review and meta-analysis of the MEDLINE, Embase, and Cochrane libraries to evaluate therapy outcomes in patients treated with frontline A+B for uHCC outside trials. Pooled estimates of overall survival (OS) and progression-free survival (PFS) at 6 and 12 months were calculated from individual patient-level data using random-effects analysis. Results: Of 2,179 patients selected from 12 cohorts, 80.5% were male, median age was 66 years (IQR 61.6–73.0), 61.6% had advanced-stage hepatocellular carcinoma (HCC), and 83.6% were Child–Pugh (CP) class A. Pooled 6- and 12-month OS was 82% (95% CI: 76–86%; I2 = 80%) and 65% (95% CI: 60–70%; I2 = 66%). Median OS of patients with CP-A liver function was 20.9 months (95% CI: 15.7–20.9), consistent with IMbrave150 estimates (19.2 months, 95% CI: 17.0–23.7, p = 0.58). Pooled PFS at 6 and 12 months was 57% (95% CI: 53–61%; I2 = 49%) and 35% (95% CI: 31–39%, I2 = 60%). Among patients with longer follow-up, the OS (n = 1,783) and PFS (n = 959) rates were 52% (95% CI: 46–58; I2 = 90%) and 26% (95% CI: 17–37; I2 = 91%) at 18 months, respectively. At 24 months, OS (n = 1,556) rate was 39% (95% CI: 31–49; I2 = 90%) and PFS (n = 732) rate was 25% (95% CI: 12–45; I2 = 95%). Conclusions: The effectiveness of A+B after registration mirrors its efficacy estimates from clinical trial datasets. Long-term survival at 24 months can be achieved in up to 39% of patients with uHCC treated with A+B in routine clinical practice. Impact and implications: This study provides real-world evidence supporting the long-term efficacy of atezolizumab plus bevacizumab (A+B) for unresectable hepatocellular carcinoma, showing survival outcomes similar to those achieved in clinical trials. These findings are important for clinicians in supporting A+B as a frontline treatment, particularly for patients with Child–Pugh class A liver function. They also offer valuable insights for policymakers and researchers for optimising treatment strategies for unresectable hepatocellular carcinoma. However, results should be interpreted with caution because of potential variability in patient populations.